GURU DAN MURID DALAM PERSEKTIF AL QUR’ANDAN HADITS - Iskandar Yusuf; Iskandar (CV. Adiba Aisha Amira, 2021)
Teachers in the perspective of Islamic education are people who are responsible for the development of all potential students. If we look functionally the word teacher can be interpreted as a giver or distributor of knowledge, skills. A teacher has a sense of responsibility towards his duties as a teacher. As said by Imam Ghazali that